The Implementation of the An-Nahdliyah Method in the Subject of Qur'an and Hadith (A Study at MINU Purwosari Metro City) - Alfi Nurillah; Ali Imron; Silvia Maya Rusniati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
One way to quickly read the Al-Qur'an is the an-Nahdliyah method, namely reading the Al-Qur'an in stages from one volume to six volumes. Researchers chose MINU Purwosari Metro Utara as a research location using the An-Nahdliyah method because the choice of Al-Qur'an teaching method was considered very important. This research is field research, using a qualitative descriptive approach. Based on the research results, it can be concluded that: Application of the An-Nahdliyah Method in Al-Qur'an Hadith subjects at MINU Purwosari: Supported by teaching aids. Place in class. Recitation activities at the beginning of each Al-Qur'an Hadith subject. Grouping of students according to the volume they have achieved. Students pray first. Then the teacher reads and continues with the students imitating together accompanied by the teacher's tapping. Students come forward one by one to read ahead while using tapping. After reciting the Koran, students are guided by the teacher to get into the habit of reading short surahs or memorizing daily prayers. The methods used are demonstration, drill, question and answer and lecture methods. There are 3 evaluations, namely daily evaluation, end of volume, and end of semester.